How do employees react to leaders' unethical behavior? The role of moral disengagement. Issue 1 (22nd October 2019) - Fehr, Ryan; Fulmer, Ashley; Keng‐Highberger, Fong T.
Abstract: Concerns over unethical leader behavior persist in today's workplace. Although some employees continue to support their leaders after learning of their unethical actions, others do not. In this paper, we integrate social cognitive theory with social information processing theory to propose that the support employees give to leaders who act unethically hinges on their propensity to morally disengage. Specifically, we develop a conditional indirect effects model, wherein moral disengagement propensity mitigates the negative impact of unethical leader behavior on leader‐directed support via employees' perceptions of value congruence with and trust in the leader. The sum result is an improved understanding of when and why employees offer support to versus withhold support from leaders who act in ethically questionable ways.